Polymer Thin Films: From Fundamentals to Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The use of polymer thin films is currently implemented in almost every aspect of modern life due to their cost-efficiency, lightness, flexibility, and unique physical and chemical properties. The reason for focusing research into polymer thin films is to understand their thermodynamic and kinetic mechanisms, such as interfacial interactions, flow behavior, film formation, relationships between deposition process parameters and the film structure, and other advanced functional properties. Thin polymer film research focuses on a wide range of industrial applications, including energy technologies, optics, sensors, microelectronics, medicine, biotechnology, etc. This Special Issue highlights and discusses studies on the formation of polymer films, their morphological analysis, and their use in various applications, including sensors, antifouling coatings, and coatings for harnessing solar energy. In addition, this Special Issue also includes two review papers on the latest research on polymer-waveguide-based optical sensors and the integration of antifouling and anti-cavitation coatings on propellers.